2016
DOI: 10.1111/ppl.12462
|View full text |Cite
|
Sign up to set email alerts
|

The E3 SUMO ligase AtSIZ1 functions in seed germination in Arabidopsis

Abstract: Seed germination is an important stage in the lifecycle of a plant because it determines subsequent vegetative growth and reproduction. Here, we show that the E3 SUMO ligase AtSIZ1 regulates seed dormancy and germination. The germination rates of the siz1 mutants were less than 50%, even after a short period of ripening. However, their germination rates increased to wild-type levels after cold stratification or long periods of ripening. In addition, exogenous gibberellin (GA) application improved the germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Therefore, the current data strongly suggest that sumoylation activates and stabilizes AtSIZ1 under drought stress. Previous studies also observed sumoylation of several proteins in response to drought . Our data suggest that AtSIZ1 participates in the sumoylation of target proteins in response to drought stress, working independently or together with other E3 SUMO ligases.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, the current data strongly suggest that sumoylation activates and stabilizes AtSIZ1 under drought stress. Previous studies also observed sumoylation of several proteins in response to drought . Our data suggest that AtSIZ1 participates in the sumoylation of target proteins in response to drought stress, working independently or together with other E3 SUMO ligases.…”
Section: Discussionsupporting
confidence: 75%
“…Plant E3 SUMO ligases are involved in responding to abiotic stresses, such as cold, drought, heat, and salt , and also have roles in various development processes . Recent studies showed that the activity and stability of Arabidopsis E3 SUMO ligase AtSIZ1 were regulated by COP1 activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the siz1 and the ots1ots2 double mutant exhibit a late germination phenotype (Castro et al , 2016; Kim et al , 2016) and abscisic acid hypersensitivity (Miura and Hasegawa, 2010), while SUMO overexpression leads to abscisic acid hyposensitivity (Lois et al , 2003). …”
Section: Resultsmentioning
confidence: 99%
“…During seed germination, the small ubiquitin‐like modifier (SUMO) E3 ligase SIZ1 attenuates ABA signaling through sumoylation of ABSCISIC ACID INSENSITIVE 5 (ABI5), an important positive regulator of ABA signaling (Miura et al ., ). However, a recent study showed that SIZ1 also impairs GA signaling during seed germination by promoting the degradation of SLEEPY (SLY1), a positive regulator of GA signaling (Kim et al ., ), so it is likely that SIZ1 exhibits a negative effect on both ABA and GA signaling. Furthermore, the rice SnRK2‐APC/C Tiller Enhancer (OsTE) ubiquitin E3 complex regulatory module might represent another regulatory hub in ABA–GA antagonism, in which OsTE physically interacts with the ABA receptors OsPYLs/OsRCARs and promotes their degradation by the 26S‐mediated proteasome pathway, while GAs decrease the level of SnRK2s and may promote APC/C TE ‐mediated degradation of OsPYL/OsRCARs (Lin et al ., ).…”
Section: Introductionmentioning
confidence: 99%